Effect of Unilateral and Bilateral Shoulder Rehabilitation Exercise Protocol in Patients Secondary to Radical Mastectomy - Jasleen Kaur Sohal1, Poonam H. Patil2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Mastectomy is an operation which causes many changes in a woman’s body. Its consequence is, among other things, lymphatic edemas, limitation of movements and strength of the upper limb of the patient, experiences in the emotional sphere, difficulties related to the postoperative scar and the results of supplementing treatment such a radiotherapy or chemotherapy. Recent studies have shown the result of effective physiotherapy treatment postoperatively. There is a paucity of literature available showing the effect of bilateral approach rather than a unilateral one for the recovery Objective: Objective of the study was to find out the effect of effect of unilateral and bilateral shoulder rehabilitation exercise protocol in patients secondary to radical mastectomy Method: A total of 20 females who underwent mastectomy procedure along with chemotherapy were included in the study. Demographic data and consent form were taken from the patients. Group A was received treatment for the unilateral i.e. the affected side and group B received treatment bilaterally for five days per week for eight weeks and pre and post assessment was done with shoulder pain and disability index (SPADI), range of motion (ROM) and manual muscle testing (MMT) Results: Statistics results within the group values for Group A SPADI (p=0.6385) and mean difference (MD) was Conclusion: A proper knowledge regarding ergonomics is important to avoid the development of musculoskeletal disorders, taking stretch breaks in between long working hours can provide a healthier working environment for nursing staff and maximize human resource efficiency.